Fetal Brain-directed AAV Gene Therapy Results in Rapid, Robust, and Persistent Transduction of Mouse Choroid Plexus Epithelia - Marie Reine Haddad; Anthony Donsante; Patricia Zerfas; Stephen G Kaler (Elsevier, 2013)
Fetal brain-directed gene addition represents an under-appreciated tool for investigating novel therapeutic approaches in animal models of central nervous system diseases with early prenatal onset. Choroid plexuses (CPs) are specialized neuroectoderm-derived structures that project into the brain's ventricles, produce cerebrospinal fluid (CSF), and regulate CSF biochemical composition. Targeting the CP may be advantageous for adeno-associated viral (AAV) gene therapy for central nervous system disorders due to its immunoprivileged location and slow rate of epithelial turnover. Yet the capacity of AAV vectors to transduce CP has not been delineated precisely. We performed intracerebroventricular injections of recombinant AAV serotype 5-green fluorescent protein (rAAV5-GFP) or rAAV9-GFP in embryonic day 15 (E15) embryos of CD-1 and C57BL/6 pregnant mice and quantified the percentages of GFP expression in CP epithelia (CPE) from lateral and fourth ventricles on E17, postnatal day 2 (P2), and P22. AAV5 was selective for CPE and showed significantly higher transduction efficiency in C57BL/6 mice (P = 0.0128). AAV9 transduced neurons and glial cells in both the mouse strains, in addition to CPE. We documented GFP expression in CPE on E17, within just 48 hours of rAAV administration to the fetal lateral ventricle, and expression by both the serotypes persisted at P130. Our results indicate that prenatal administration of rAAV5 and rAAV9 enables rapid, robust, and sustained transduction of mouse CPE and buttress the rationale for experimental therapeutics targeting the CP.